2004
DOI: 10.1128/mcb.24.2.774-786.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Origin Recognition Complex and Sir4 Protein Recruit Sir1p to Yeast Silent Chromatin through Independent Interactions Requiring a Common Sir1p Domain

Abstract: Sir1p is one of four SIR (silent information regulator) proteins required for silencing the cryptic mating-type locus HMRa in the budding yeast Saccharomyces cerevisiae. A Sir1p interaction with Orc1p, the largest subunit of the origin recognition complex (ORC), is critical for Sir1p's ability to bind HMRa and function in the formation of silent chromatin. Here we show that a discrete domain within Sir1p, the ORC interaction region (OIR), was necessary and sufficient for a Sir1p-ORC interaction. The OIR contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
94
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(97 citation statements)
references
References 52 publications
2
94
0
Order By: Relevance
“…Direct physical interaction between Sir1p and ORC is critical for establishing silent chromatin at HMR and HML in S. cerevisiae (7,10,11). Previous studies identified the minimal OIR of Sir1p and amino acids within the OIR as important for the Sir1p͞ORC interaction (8,11) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Direct physical interaction between Sir1p and ORC is critical for establishing silent chromatin at HMR and HML in S. cerevisiae (7,10,11). Previous studies identified the minimal OIR of Sir1p and amino acids within the OIR as important for the Sir1p͞ORC interaction (8,11) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The crystal structure of the S. cerevisiae Orc1p-BAH domain has been determined and serves as the guide for modeling other BAH domains (10). The domain of Sir1p required for the Sir1p͞ORC interaction, the ORC interaction region (OIR) (11), is the only molecularly defined BAH-domain-binding partner and thus is key for understanding the function and mechanisms of BAH-domaincontaining proteins and their binding partners in regulating chromatin structure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, an eso mutant of Sir2, which has no obvious connection to interaction with Sir4, is also located in the Sir4-interacting region of Sir2 (Garcia and Pillus 2002). It is known that establishment of a silenced chromatin domain in the mating type loci involves a cascade of protein-protein interactions, including the binding of Sir1 to the silencerbound ORC1 and the recruitment of the Sir2-Sir4 complex by the interaction between Sir1 and Sir4 (Triolo and Sternglanz 1996;Bose et al 2004;Hou et al 2005;Hsu et al 2005). Thus, a weakened or disrupted Sir2-Sir4 interaction can undermine the Sir1 function of recruiting a histone deacetylase to the targeted chromatin region, and our discovery that a Sir2 mutant affecting Sir1 function is located in the Sir4 interaction region is testimony to the network of protein-protein interaction required for transcriptional silencing in yeast.…”
Section: Discussionmentioning
confidence: 99%
“…ORC1 plays a key role in this process (Figure 1a). ORC1 interacts with the SIR1 protein and recruits the remaining components of the SIR complex including histone deacetylase SIR2 to the chromatin [7,2730].
10.1080/19491034.2018.1516484-F0001Figure 1.Chromatin related functions of ORC in different species.
…”
Section: Heterochromatin Formation and Transcription Regulationmentioning
confidence: 99%